Comparison of four pharmacological strategies aimed to prevent the lung infammation and paraquat-induced alveolar damage (2019)
ABSTRACT: Objective: The aim of this study was to compare in vivo efect of fve pharmacological options on infammation and pulmonary fbrosis induced by paraquat. Methods: 54 Wistar SPF rats were used. After 2 h post-intoxication with paraquat ion, groups of 9 animals were ran domly assigned to (1) cyclophosphamide plus dexamethasone (2) low molecular weight heparin (3) unfractionated heparin (4) vitamin C every 24 h, (5) atorvastatin or (6) placebo with intraperitoneal saline. Lung infammation, alveolar injury, hepatocyte damage, hepatic regeneration, acute tubular necrosis and kidney congestion were evaluated. Results: In the control group 100% of animals presented moderate and severe lung infammation, while in the groups with atorvastatin and intratracheal heparin this proportion was lower (55.5%; CI 26.6–81.3%) (p=0.025). A lower degree of moderate or severe hepatic regeneration was evident in the treatment groups with atorvastatin (p=0.009). In this study was demonstrated that statins and heparin might have a protective efect in the paraquat induced destructive phase. More evidence is needed to evaluated of dose–response efects of these drugs before to study in clinical trials